Formation of children’s school readiness of teachers to the establishment of tolerance education of children (according to the results of the pilot study) (Pedagogy of Higher and Secondary Education, 2012)
Romaniuk K. Formation of children’s school readiness of teachers to the establishment of tolerance education of children (according to the results of the pilot study).The article defines the problem of forming inter-ethnic tolerance as one of the current in modern pedagogical science. The results of experimental research allowed to determine teachers readiness and their role in process of forming inter-ethnic tolerance of preschool age children. We also determined the content of pedagogical activity and the ways of advanced training future pedagogues.
Keywords: inter-ethnic tolerance; educational process; the basic program; competence